Mid-to-Late Holocene environmental reconstruction on Pico Island (Azores, Portugal) based on multiproxy analysis of Lake Caveiro sediments - Raposeiro, P. M.; Gonçalves, V.; Marques, H.S.; Vilaverde, J.; Sáez, Alberto; Alonso, M.; Hernández, Armand; Pueyo, J. J.; de Boer, E.J.; Rull, Valentí; Costa, A. C.; Giralt, Santiago; et al. (2018)
The Azores constitutes the most remote archipelago of the North Atlantic Ocean. Both human colonization and natural changes have significantly modified its ecosystems. To assess the impacts of natural and anthropogenic changes over the last 8200 yr, elemental geochemistry on bulk organic matter, diatoms, Cladocera and chironomid remains were analyzed in a 952-cm long sediment (3.7m depth) from Lake Caveiro. From 8200 to 650 cal yr BP, climatic and volcanic forcing seem to have been the main drivers of biological change. Between 8200 and 6000 cal yr BP, the sedimentary sequence was characterized by dominance of volcaniclastic deposits and high abundance of aerophilic diatoms and sparse Cladocera and chironomid remains. This interval has been interpreted as indicative of unstable conditions because of intermittent renewal of lake bottom substratum owing to repetitive tephra sedimentation. Between 6000 and 3500 cal yr BP, fossil assemblages were dominated by benthic species, with an increasing trend of the planktonic/benthic (P:B) ratio, suggesting stable substratum and rising lake levels. An increase in planktonic taxa and the presence of deep-water chironomid species was found between 3500 and 1300 cal yr BP, suggesting a highstand phase. Between 1300 and 650 cal yr BP, a decreasing trend of the P:B ratio was recorded, implying a further lake shallowing. Moreover, the appearance of flowing water species suggests a period characterized by climate instability. From 650 cal yr BP to the present, a significant increase in primary production and a decline in species richness likely reflect anthropogenic impacts, such as forest clearance and the introduction of exotic species. These results highlight the impact that human, volcanic and climatic drivers have had on the environmental evolution of the ecosystems of Pico Island. This research is funded by Spanish projects PaleoNAO (CGL2010-15767), RapidNAO (CGL2013-40608-R) and PaleoModes (CGL2016-75281-C2). Peer Reviewed